Association of ARDS Severity with Non-Invasive Ventilation Duration in COVID-19 Patients - Romadoni, Muhammad Aulia Hikmah; Moulid Hidayat; Bayu Tirta Dirja (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The global spread of Coronavirus disease (COVID-19), worsened by the emergence of new variants such as Delta, has created significant challenges for health systems. One of the severe complications experienced by infected individuals is acute respiratory distress syndrome (ARDS), a condition characterized by pulmonary fluid leakage that leads to impaired oxygenation and respiratory difficulty. Patients with mild ARDS are often managed with non-invasive ventilation (NIV), which provides supplemental oxygen without the need for intubation. This study was conducted to examine whether the severity of ARDS influences the duration of NIV use in COVID-19 patients treated at the West Nusa Tenggara Provincial General Hospital (RSUD) in 2021. A cross-sectional study with a retrospective design was applied, and participants were selected through consecutive sampling. Data were obtained from hospital medical records and analyzed using the independent sample t-test. A total of 46 patients met the inclusion criteria, consisting of 27 males (58.7%) and 19 females (41.3%), with a mean age of 53.9 ± 7.9 years. The mean duration of NIV was 3.26 ± 2.816 days in patients with mild ARDS and 3.65 ± 2.870 days in those with moderate ARDS. Statistical analysis showed no significant difference between the two groups (p = 0.643; p > 0.05). These findings indicate that ARDS severity is not associated with the length of NIV use in COVID-19 patients.